2019
DOI: 10.5194/acp-19-7151-2019
|View full text |Cite
|
Sign up to set email alerts
|

Implication of strongly increased atmospheric methane concentrations for chemistry–climate connections

Abstract: Abstract. Methane (CH4) is the second-most important directly emitted greenhouse gas, the atmospheric concentration of which is influenced by human activities. In this study, numerical simulations with the chemistry–climate model (CCM) EMAC are performed, aiming to assess possible consequences of significantly enhanced CH4 concentrations in the Earth's atmosphere for the climate. We analyse experiments with 2×CH4 and 5×CH4 present-day (2010) mixing ratio and its quasi-instantaneous chemical impact on the atmos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 50 publications
2
31
1
Order By: Relevance
“…Hansen et al, 2005;Shindell et al, 2009;Myhre et al, 2013a), who concluded that the total climate forcing by CH4 is almost double that of the direct forcing due to indirect effects. The UKESM1 estimate is also larger than the +0.69 W m -2 radiative impact of an increase in CH4 concentration of 1800 ppbv above present-day levels quantified by Winterstein et al (2019) (Lohmann et al, 2010). The relative contributions of the direct and indirect forcings to the total CH4 ERF quantified here and an emissions-based perspective of the CH4 forcing can be found in O'Connor et al (2019).…”
Section: Methane (Ch4)mentioning
confidence: 69%
“…Hansen et al, 2005;Shindell et al, 2009;Myhre et al, 2013a), who concluded that the total climate forcing by CH4 is almost double that of the direct forcing due to indirect effects. The UKESM1 estimate is also larger than the +0.69 W m -2 radiative impact of an increase in CH4 concentration of 1800 ppbv above present-day levels quantified by Winterstein et al (2019) (Lohmann et al, 2010). The relative contributions of the direct and indirect forcings to the total CH4 ERF quantified here and an emissions-based perspective of the CH4 forcing can be found in O'Connor et al (2019).…”
Section: Methane (Ch4)mentioning
confidence: 69%
“…Methane contributes directly to the chemical loss of stratospheric ozone, and also indirectly (like other GHGs) by warming the troposphere and cooling the stratosphere [ 397 , 398 ]. Natural sources of CH 4 are likely to increase in the future because of climate change.…”
Section: Air Qualitymentioning
confidence: 99%
“…When comparing the ERF and IRF for black carbon (BC), as an example, RAs lead to the ERF being half that of its IRF (Stjern et al, 2017;Smith et al, 2018). On the other hand, Xia et al (2016) found in their model that cloud and sea ice adjustments driven by stratospheric O 3 recovery included in the ERF definition lead to the ERF being different in both sign and magnitude from the SARF. And when comparing different forcing metrics, Hansen et al (2005) found that the efficacy of a climate forcing (i.e.…”
Section: Introductionmentioning
confidence: 99%